2017
DOI: 10.4172/1948-5956.1000443
|View full text |Cite
|
Sign up to set email alerts
|

An Abscopal Response to Radiation Therapy in a Patient with Metastatic Non-Small Cell Lung Cancer: A Case Report

Abstract: IntroductionThe Abscopal effect refers to radiation-induced tumor regression in lesions that are distant from a targeted site, and has been recognized for six decades as a rare, unexplained phenomenon in patients receiving local radiotherapy [1]. According to our knowledge, the radiation therapy is not available in patients with multiple metastatic cancer. The abscopal effect is observed outside the treated field of radiation, but it is underrecognized in the clinical practice [2,3]. Recent studies have sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…While most patients who experienced an abscopal response were treated with immunotherapy, there were a small number of individual cases in which abscopal responses were observed following radiation alone [7-8,10]. This is consistent with the prevailing theories of cancer immunosurveillance as an inherent function of the immune system [47].…”
Section: Reviewsupporting
confidence: 57%
See 1 more Smart Citation
“…While most patients who experienced an abscopal response were treated with immunotherapy, there were a small number of individual cases in which abscopal responses were observed following radiation alone [7-8,10]. This is consistent with the prevailing theories of cancer immunosurveillance as an inherent function of the immune system [47].…”
Section: Reviewsupporting
confidence: 57%
“…Forty-eight of 53 patients were diagnosed with metastatic melanoma and received a combination of radiation therapy and ipilimumab. Three patients with melanoma, non-small cell lung cancer, and likely colorectal adenocarcinoma metastatic to the brain experienced an abscopal response with radiation therapy alone, without any systemic therapy [7-8,10]. In addition, abscopal responses were observed in one patient with melanoma treated with vemurafenib and one patient with non-small cell lung cancer treated with cytotoxic chemotherapy [14,17].…”
Section: Reviewmentioning
confidence: 99%
“…Katayama et al [33] reported abscopal effects of radiation therapy in a patient with metastatic NSCLC. This case study included a 63-year-old male patient who had presented with worsening dysgraphia and memory impairment.…”
Section: Clinical Evidence Of Abscopal Effectsmentioning
confidence: 99%
“…In two of the six cases [10-11], radiation therapy alone to either the primary lung cancer or a metastatic lesion leads to regression and represent a bona fide abscopal effect. Of these two patients, one had a short-lived abscopal effect [10], the other patient reported [11] had a long-lived response.…”
Section: Discussionmentioning
confidence: 99%
“…In two of the six cases [10-11], radiation therapy alone to either the primary lung cancer or a metastatic lesion leads to regression and represent a bona fide abscopal effect. Of these two patients, one had a short-lived abscopal effect [10], the other patient reported [11] had a long-lived response. In the remaining four patients [9,12-13], including the current case, the abscopal effect was augmented by either ipilimumab [9] or nivolumab [12-13].…”
Section: Discussionmentioning
confidence: 99%